Dinamika representasi keberagaman agama dalam media massa Indonesia - Khudin, Ahmad Mifta (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the dynamics of religious diversity representation in Indonesian mass media. Indonesia, as a country with rich religious diversity, exhibits complex dynamics in the representation of religious diversity by the mass media, which is very influential in shaping public opinion and influencing social perceptions of minority and majority religions. This study uses a descriptive qualitative approach and library research method to systematically collect and analyze literature data, aiming to provide an in-depth picture of the dynamics of religious diversity representation in Indonesian mass media. This research shows that mass media in Indonesia plays an important role in providing a pluralistic and balanced representation of religious diversity, despite facing challenges in handling religious conflicts without triggering tensions, which are influenced by Muslim-majority demographics, pro-pluralism policies, and religious group pressure, and require a commitment to ethical journalism and interfaith collaboration to support social harmony.